Lactate as Potential Mediators for Exercise-Induced Positive Effects on Neuroplasticity and Cerebrovascular Plasticity - Huang, Zhihai; Zhang, Yulan; Zhou, Ruixue; Yang, Luodan; Pan, Hongying (Frontiers in Physiology, 2021)
The accumulated evidence from animal and human studies supports that exercise is beneficial to physical health. Exercise can upregulate various neurotrophic factors, activate neuroplasticity, and play a positive role in improving and enhancing cerebrovascular function. Due to its economy, convenience, and ability to prevent or ameliorate a variety of aging-related diseases, exercise, a healthy lifestyle, is increasingly popularized by people. However, the mechanism by which exercise performs this function and how it is transmitted from muscles to the brain remains incompletely understood. Here, we reviewed the various beneficial effects of exercise on the brain，and focused on the possible participation of lactate in the beneficial effects of exercise on neuroplasticity and cerebrovascular function. Based on these recent studies, we propose that lactate, a waste that was misunderstood as a byproduct of glycolysis in the past, maybe a key signaling molecule that regulates beneficial adaptation of the brain caused by exercise, and participates in the related signaling pathway of irisin/FNDC5.